Entomological Studies in the Lake Hazen Area, Ellesmere Island, Including Lists of Species of Arachnida, Collembola, and Insecta - Oliver, D.R. (ARCTIC, 1963)
Notes investigations in 1961 and 1962 at Camp Hazen and lists the species collected in 1961: 11 arachnid, 14 collembole, and 189 insect species; 25 others were collected in 1962. Species previously recorded in the Queen Elizabeth Islands are indicated; and a second list is given of those (15 arachnid, 17 collumbole, and 39 insects) recorded on the Islands but not taken at Camp Hazen.